2022
DOI: 10.1002/ijgo.14301
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathology and neonatal encephalopathy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
(126 reference statements)
0
7
1
Order By: Relevance
“…[10] Also previous studies revealed, that both macroscopic and microscopic exams are associated with hypoxic brain lesions. [11][12][13] In our study, the most common placental microscopic changes in perinatal asphyxia were from the maternal and fetal vascular malperfusion categories, unlike the control group where most placentas were normal. According to the classification of placental lesions, we can conclude that those that determined the appearance of hypoxic lesions were chronic, these results being similar to Bingham et al [14].…”
Section: Discussioncontrasting
confidence: 46%
“…[10] Also previous studies revealed, that both macroscopic and microscopic exams are associated with hypoxic brain lesions. [11][12][13] In our study, the most common placental microscopic changes in perinatal asphyxia were from the maternal and fetal vascular malperfusion categories, unlike the control group where most placentas were normal. According to the classification of placental lesions, we can conclude that those that determined the appearance of hypoxic lesions were chronic, these results being similar to Bingham et al [14].…”
Section: Discussioncontrasting
confidence: 46%
“…11 Umbilical cord pathology, inflammatory changes in the placenta, and placental weight were associated with HIE. 12 Intrapartum period risk factors appear to be important for the development of HIE. 13 Placenta previa, medicals during pregnancy, fetal distress, abnormal labor stage, Apgar score, amniotic fluid contamination, and cesarean section were independent risk factors for HIE.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the D-NCP group, despite showing similar pathway alterations, exhibited a less severe response, which might explain the absence of cleft palate formation in this group. In the D-CP group, the exacerbated response in in ammatory and hypoxic pathways might re ect a compromised placental function, leading to more severe developmental outcomes like Preeclampsia [20][21][22]. On the other hand, the D-NCP group, while still affected, may have retained a better adaptive response, preventing the full manifestation of developmental anomalies.…”
Section: Discussionmentioning
confidence: 99%